A New Cold-Active Glucose Oxidase From Penicillium: High-Level Expression and Application in Fish Preservation - Yuan, Mingxue; Ning, Chen; Yang, Suxiao; Liang, Qingping; Mou, Haijin; Liu, Zhemin (Frontiers in Microbiology, 2020)
Glucose oxidase (GOx) with high enzyme activity at low temperature (4°C) is potentially useful for food preservation, especially for aquatic products preservation. A cold-active GOx with approximately 83% similarity to known protein sequences, was isolated from Penicillium sp. MX3343 and expressed in Pichia pastoris X33. Through high cell density fermentation, the yield of recombinant enzyme (named GOxP5) reached 458.6 U/mL. GOxP5 showed optimal activity at 30°C and pH 5.5, and was stable at a broad pH range from pH 2 to 6. Moreover, GOxP5 could maintain 72% maximum activity at 4°C, suggesting its application for the preservation of aquatic products at low-temperatures. Importantly, GOxP5 showed a good antimicrobial effect against common fish pathogenic bacteria (Listeria monocytogenes and Vibrio parahaemolyticus). Moreover, sensory, microbiological (total bacterial count), and physicochemical (total volatile basic nitrogen and pH) systematic analyses proved GOxP5 to be an excellent freshness preserving agent in the context of the grass carp. These favorable enzymatic properties of GOxP5 make it potentially useful in food biopreservation, and the effect was better compared to the commonly used chemical preservatives.